2013
DOI: 10.1109/jstars.2013.2252601
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Hyperspectral Narrowbands (HNBs) and Composition of Hyperspectral Twoband Vegetation Indices (HVIs) for Biophysical Characterization and Discrimination of Crop Types Using Field Reflectance and Hyperion/EO-1 Data

Abstract: The overarching goal of this study was to establish optimal hyperspectral vegetation indices (HVIs) and hyperspectral narrowbands (HNBs) that best characterize, classify, model, and map the world's main agricultural crops. The primary objectives were: (1) crop biophysical modeling through HNBs and HVIs, (2) accuracy assessment of crop type discrimination using Wilks' Lambda through a discriminant model, and (3) meta-analysis to select optimal HNBs and HVIs for applications related to agriculture. The study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 25 publications
5
105
0
Order By: Relevance
“…Hyperspectral vegetation indices (HVIs) use narrowband features, which can only be captured by hyperspectral instruments [32]. Research by Thenkabail et al [34,70] has shown that, due to data redundancy in the hyperspectral signal, a small number of specific hyperspectral narrowbands (HNBs) have enough information to determine structural vegetation characteristics. Therefore, hyperspectral two-band vegetation indices (HTBVI) based on normalized difference between the bands are used as a data-mining tool in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperspectral vegetation indices (HVIs) use narrowband features, which can only be captured by hyperspectral instruments [32]. Research by Thenkabail et al [34,70] has shown that, due to data redundancy in the hyperspectral signal, a small number of specific hyperspectral narrowbands (HNBs) have enough information to determine structural vegetation characteristics. Therefore, hyperspectral two-band vegetation indices (HTBVI) based on normalized difference between the bands are used as a data-mining tool in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the probability distributions of the broadband and narrowband NDVIs for each site were investigated in order to assess differences between MAT and MNT. The HNBs in the red and NIR wavelength regions for the three narrowband NDVIs have been chosen by assessment of the spectral metrics, based on research in optimal HNBs for vegetation analysis by Thenkabail et al [34,70] (EnMAP band 59, center wavelength 756 nm), the central NIR reflectance plateau (EnMAP band 71, center wavelength 864 nm) and the maximum NIR reflectance (EnMAP band 101, center wavelength 1,020 nm). EnMAP band 59 at the beginning of the NIR reflectance plateau may be specifically sensitive to vegetation structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These eigenvalues contain the percentage of original data (bands) captured in that component. Band loadings are the coefficient between each variable (band) and any component; therefore, information of the band loading can be used to find the best bands [40,49]. In order to identify the best bands, we decomposed principal components into their band loading values.…”
Section: Methodsmentioning
confidence: 99%
“…The advent of airborne HSI sensors has raised new opportunities in urban remote sensing applications, due to a combination of high spectral and high spatial resolution in HSI images [3,9]. HSI sensor stores information of a pixel in hundreds of spectral bands which enables the accurate identification of objects or classes which have similar spectral characteristics [13]. HSI collects a wide continuous narrowband reflectance information across the electromagnetic spectrum precisely 400-2500 nm which provides higher separability features for characterizing complex urban objects [9,14].…”
Section: Introductionmentioning
confidence: 99%